how would i factor out the "k" in this equation?
y= -2f(2x + 6) + 6
- Anonymous1 month ago
You need your eyes tested!
- Zac ZLv 71 month ago
Since there is no k in the equation, the only way to factor it out would be to add an 1/k as neutralizing element. I don't know why you'd want to do that but you could:
y = -2f (2x + 6) + 6
--> y = k (1/k (-2f (2x + 6) + 6))
or y = k (-2f/k (2x + 6) + 6/k)
- lenpol7Lv 71 month ago
Where is the 'k'?
- 1 month ago
I’ll take a guess you meant the “f”?
y = -2f(2x + 6) + 6
y - 6 = -2f(2x + 6) + 6 - 6
y - 6 = -2f(2x + 6)
(y - 6)/ -2 = [-2f(2x + 6)]/-2
-½y + 3 = f(2x + 6)
(-½y + 3)/(2x +6) = f(2x +6)/(2x + 6)
(-½y + 3)/(2x +6) = f
- What do you think of the answers? You can sign in to give your opinion on the answer.
- KrishnamurthyLv 71 month ago
There is no k in the equation.
- Iggy RockoLv 71 month ago
Your equation has no k. Can you provide more context? What does k in quotes really mean?
- rotchmLv 71 month ago
Hint: rewrite as y - 6 = -2f(2(x+3)).
Unanon yourself and I will detail more if need be.
- MorningfoxLv 71 month ago
Since there is no “k” in that equation, I can’t factor it out.